Evaluasi Program Asistensi Sosial bagi Orang dengan Kecacatan Berat (ODK Berat) - Haryati Roebyantho; Setyo Sumarno (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2013)
The Ministry of Social Affairs has been imposing a policies to protect persons with severe disabilities in an effort to fulfill the rights to improve their social welfare and protection with Minister’s Decission Number: 68/HUK/2010 on guidelines for the implementation of social security for people with severe disabilities. The goal of the policy was to fulfill basic needs of persons with severe disabilities and increase awareness of the family and community. Trial policy was implemented from 2006 to 2011. During the 5-year trial, the policy had been able to provide assistance to 17,000 people. However, studies have not been done on the impact of policies and programs. Therefore, the Center for Social Welfare Research did a quick research to know the success of the program. The research method was evaluative descriptive. Data collected through interviews, document analysis and focus group discussion. Respondents were determined from the cluster, consisting social service implementator; postal officials; surrogate parents; social guidance; Societal social workers (TKSM), in district and municipality/regence level. Respondents casted to evaluate the target figure program, such as surrogate parents of severe disabities; social guider; companion, community leaders and local postal officers in district, city/regence. The Analysis focused on communications policy implementation and the source and structure of organizational. The basic analysis of the program’s impact are goal achievement, living need adequacy, and commitment growth of families and communities. It was found that the implementation of the policy has been less socialized at the executive level to lower level/ grassroots (village and policy beneficiaries). As a result, the knowledge of the policy reached only until the level of the city or regence implementator, though the implementation of the program has reached the target substancially. The policy impact is to improve the welfare of persons with severe disabilities and improve treatment and that therapy. On the other hand, there has been an increase in families and communities caring awareness for persons with severe disabilities. There has been a family need that has not been psychologically accomplished yet, namely assurance if there is a member of the family get sicked or pass away. Human resources in terms of competence and quality guidance does not refer the Social Welfare Regulatio Number 11 of 2009. It is recommended that is worth to create planned between Ministry of Social Affairs and Ministry of Health to provide a service in family-based therapy and home visit. Also, it needs a cordination between the Ministry of Social Affairs, Post Office, and local government to improve human resource development (social guidance and aid disbursment). Ministry of social affairs also ought to share with local governments for funding socialization program efforts to optimize objective performance, and a need to sharpen and refine the concept or criteria of persons with severe disabilities